Pollen morphology and infrageneric classification of selected Callicarpa species (Lamiaceae) from the Philippines and Borneo - Jennifer Danila; GRECEBIO JONATHAN D. ALEJANDRO (Society for Indonesian Biodiversity, 2020)
Abstract. Danila JS, Alejandro GJD. 2020. Pollen morphology and infrageneric classification of selected Callicarpa species (Lamiaceae) from the Philippines and Borneo. Biodiversitas 21: 5736-5746. We used pollen grains of ten species representing the controversial genera Geunsia Blume and Callicarpa L. from the key centers of Malesia - Philippines, and Borneo including other countries in Asia. Herbarium specimens and collected samples from the field were examined using Scanning Electron Microscopy (SEM) in search of new characters to establish conclusive evidence that might contribute to the study of the relationship between Geunsia and Callicarpa. Based on SEM observations, both the investigated pollen grains of Geunsia and Callicarpa are mostly small to medium, spheroidal or circular, prolate to oblate, isopolar, and tricolpate. Moreover, the exine surface is mostly coarsely reticulated with a thin perforated colpus edge and sunken finely granulated colpus membrane. However, exine ornamentation shows possible separation of Geunsia and Callicarpa due to various morphological results observed. Several types of exine ornamentation were found in species of the section Callicarpa, i.e., C. erioclona, C. arborea, C. macrophylla, and C. candicans which attributes in the projected separation of these species while four species in the section Geunsia are united as a group having coarsely reticulate exine. Surprisingly, C. arborea samples give additional support to the hypothesis that rugulate exine sculpture might be its plesiomorphic character due to evolutionary evidence of other exine types of this species. On the other hand, pollen size and shape class of the sections of Geunsia and Callicarpa were both observed with similar features having an average pollen size equivalent to medium and a prolate shape supporting the concept of previous studies to nest Geunsia within Callicarpa. This reveals that pollen morphology is useful in the study of infrageneric classification within these groups. However, further morphological studies involving larger number of specimens are needed especially in the study of exine to prove its consistency as diagnostic character in the study of phylogenetic relationship.